1993
DOI: 10.1046/j.1525-1438.1993.03040208.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary drainage following radical hysterectomy for cervical carcinoma — a pilot comparison of urethral and suprapubic routes

Abstract: Twenty-four patients who underwent radical hysterectomy and pelvic node dissection for cervical carcinoma were randomized in a pilot study to compare continuous postoperative drainage by urethral and suprapubic catheters. There were no statistically significant differences in either the duration of continuous catheter drainage before the return of spontaneous voiding or the incidence of urinary tract infection in the two groups. Power calculations reveal that 628 patients require to be entered into each arm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…13 Six trials addressed duration of catheterization as a specific outcome. 7,9,10,12,19,20 Overall, no significant difference was found between groups (weighted mean difference Ϫ0.52 days, 95% CI Ϫ2.47 to 1.43 days, Pϭ.59). There was evidence of heterogeneity (Cochran Q statisticϭ31.53, dfϭ5, PϽ.01) but not bias (Eggerϭ0.71, 95% CI Ϫ2.958 to 4.372, Pϭ.62).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…13 Six trials addressed duration of catheterization as a specific outcome. 7,9,10,12,19,20 Overall, no significant difference was found between groups (weighted mean difference Ϫ0.52 days, 95% CI Ϫ2.47 to 1.43 days, Pϭ.59). There was evidence of heterogeneity (Cochran Q statisticϭ31.53, dfϭ5, PϽ.01) but not bias (Eggerϭ0.71, 95% CI Ϫ2.958 to 4.372, Pϭ.62).…”
Section: Resultsmentioning
confidence: 89%
“…Intermittent urethral catheterization techniques (clean intermittent catheterization and clean intermittent self-catheterization) have demonstrated decreased rates of urinary tract infection when compared with indwelling urethral catheterization, 7,8 although increased nursing workload, cost, and varying patient preferences are factors that mitigate against opting for these newer forms of postoperative bladder drainage. 7,9,10 A recent Cochrane review examined options for short-term catheterization and concluded that further evidence was required before definite consensus could be reached. 11 However, the scope of the 2006 Cochrane was broad, including studies on both male and female populations.…”
mentioning
confidence: 99%
“…The majority of these trials has been performed in patients, both men and women, who underwent general abdominal surgery [8,9,10,11,12]. A small number of trials studied women after gynecological surgery, concerning procedures such as correction of stress incontinence, radical hysterectomy for cervical carcinoma and a combination of various pelvic organ prolapse surgery techniques [1,13,14]. Only three randomized controlled trials, published in 1985, 1989 and 1996, respectively, compared transurethral and suprapubic catheterization in vaginal anterior wall prolapse surgery and focused on voiding function [4,5,15].…”
Section: Discussionmentioning
confidence: 99%